Aromatic amine‐terminated polysulfide oligomer: Synthesis and application in self‐healable polyurea. Issue 13 (22nd May 2019) - Gao, Wentong; Xu, Jianwei; Zuo, Pengfei; Dong, Hao; Quan, Yiwu; Chang, Pengshan
ABSTRACT: The dynamic chemistry of disulfide bonds has emerged as one of the most powerful tools used for the fabrication of organic compounds and self‐healing materials. In this article, a novel aromatic amine‐terminated polysulfide oligomer is first synthesized from thiol‐terminated polysulfide oligomer and bis(4‐aminophenyl) disulfide via disulfide metathesis mechanism. The resulting oligomer is confirmed by FTIR and 1 H NMR spectra and then successfully applied in constructing self‐healable polyurea material (A‐LP23‐I), which combines the advantages of higher strength of polyureas and excellent self‐healing ability of polysulfide‐based materials. After subjecting to a temperature of 75 °C for 48 h, both the tensile strength and ultimate elongation of A‐LP23‐I restore to more than 90% of the original values (3.32 MPa and 396%). This study demonstrates a novel strategy for synthesizing aromatic amine‐terminated oligomer. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 1460–1466 Abstract : By taking advantage of a disulfide metathesis mechanism, a novel aromatic amine‐terminated polysulfide oligomer is easily synthesized via a simple one‐pot method with a high yield of up to 95.6%. This work also offers a demonstration of self‐healable polysulfide polyurea, which combines the advantages of higher strength of polyurea and the excellent self‐healing ability of polysulfide‐based material.